2017
DOI: 10.1021/acsami.7b02161
|View full text |Cite
|
Sign up to set email alerts
|

High-Visible-Light Photoactivity of Plasma-Promoted Vanadium Clusters on Nanozeolites for Partial Photooxidation of Methanol

Abstract: Cold VCl-plasma is employed for the preparation of highly dispersed vanadium oxide clusters on nanosized zeolite. Different types of zeolites, such as EMT, FAU (z.X), and Beta, are used. The activity of the prepared catalysts is studied in the selective photooxidation of methanol under polychromatic visible and UV irradiations. The physicochemical properties and catalytic performance of plasma-treated zeolite Beta (P-VO@Beta) catalyst is compared with zeolite Beta (VO@Beta) and amorphous silica (VO@SiO) impreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
2
16
0
1
Order By: Relevance
“…In any case, it is interesting to note that the high selectivity to formaldehyde is lost when extended vanadia structures such as V 2 O 5 nanoparticles are additionally present. This is in line with the observation of different products in the work of El‐Roz et al Since the exact state of hydration is not known under reaction conditions, we cannot unambiguously comment on a potential activity of hydrated monomers and dimers. Wavelengths longer than 320 nm are still sufficiently energetic to excite charge carriers in those species (absorption at about 410 to 440 nm).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In any case, it is interesting to note that the high selectivity to formaldehyde is lost when extended vanadia structures such as V 2 O 5 nanoparticles are additionally present. This is in line with the observation of different products in the work of El‐Roz et al Since the exact state of hydration is not known under reaction conditions, we cannot unambiguously comment on a potential activity of hydrated monomers and dimers. Wavelengths longer than 320 nm are still sufficiently energetic to excite charge carriers in those species (absorption at about 410 to 440 nm).…”
Section: Resultssupporting
confidence: 86%
“…The V 2 O 5 NPs, however, were inactive in the photocatalytic reaction, in spite of their ability to function as catalysts in the conventional process at elevated temperature. This is in line with the observation by El‐Roz et al that amorphous VO x clusters are beneficial for the methanol oxidation reaction . In both previous studies, the support was always silica‐based (bulk SiO 2 , mesoporous SiO 2 , or zeolites).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previously, El‐Roz et al . showed that photocatalytic methanol oxidation was in principle feasible with vanadium oxide moieties supported on silica and on zeolites.…”
Section: Figurementioning
confidence: 69%
“…Other recently mentioned substrates are methanol, being selectively photooxidized on Au/WO 3 [176], Au-and/or Ag-modified TiO 2 [177], Ag-modified TiO 2 and SiO 2 [178], vanadia systems [179], 2-propanol, with a study featuring Au/TiO 2 [180]. A few other works discuss the same process for carbohydrates like glucose in the presence of Fe 3+ ions on TiO 2 [181] or undoped sol-gel TiO 2 [182].…”
Section: Selective Photooxidation Of Alcoholsmentioning
confidence: 99%